2018
DOI: 10.1016/j.athoracsur.2018.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Incentive Spirometry After Lung Resection: A Randomized Controlled Trial

Abstract: The addition of IS to routine postoperative physiotherapy does not reduce the incidence of PPC after lung resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 13 publications
0
35
0
Order By: Relevance
“…The literatures did not recommend to routinely use IS for prevention of postoperative collapse [14, 15, 17, 27–29]. The current study showed 65.5% of patients with lung cancers to use the IS undergoing surgical resection.…”
Section: Discussionmentioning
confidence: 58%
“…The literatures did not recommend to routinely use IS for prevention of postoperative collapse [14, 15, 17, 27–29]. The current study showed 65.5% of patients with lung cancers to use the IS undergoing surgical resection.…”
Section: Discussionmentioning
confidence: 58%
“…They identified a need for more adequately powered studies with well-defined outcome measures to better evaluate the treatment benefit of IS in thoracic surgery patients. Since the publication of this review, there have been 4 further studies [13][14][15][16] with 8,166 subjects investigating the clinical effectiveness of IS in the postoperative management of thoracic surgery patients. Three were RCTs, and one was a population-based observational study ( T1,AQ:E Table 1).…”
Section: Is Devices and Theorymentioning
confidence: 99%
“…Malik et al 14 performed an RCT with 387 subjects undergoing lung resection in Canada between 2014 and 2017. They investigated whether any incremental benefit was conferred by the addition of IS to standard physiotherapy.…”
Section: Is Devices and Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The IS is used for the prevention of atelectasis, hypoxemia, pneumonia, respiratory dysfunction, and pleural effusion [3,4]. However, IS utilization has remained the same since its initial development in the 1960s, and the usage protocol has not been standardized [5-8].…”
Section: Introductionmentioning
confidence: 99%